A Long-Recognized but Undescribed New Species of Cyprinella (Cypriniformes: Leuciscidae) from North Carolina and South Carolina, United States - Bryn H. Tracy; Fred C. Rohde; Michael A. Perkins; Laura M. Lee; Kara B Carlson; Madelyn McCutcheon; Brena K. Jones; Heather K. Evans (Southeastern Fishes Council Proceedings, 2024)
Cyprinella leptocheilus sp. nov., Siouan Thinlip Chub, is described as a new species that is endemic to Sand Hills and upper Coastal Plain streams in North Carolina and South Carolina. Recognized as an undescribed species since the early 1970s, this fish was known in the literature and in museum electronic databases as Hybopsis n. sp., H. sp. cf. zanema, Cyprinella n. sp., and C. sp. cf. zanema. Unofficially, it had gone by the common name Thinlip Chub. It was thought to be closely related to the two other barbeled Cyprinella species: Thicklip Chub, C. labrosa, and Santee Chub, C. zanema. Cyprinella leptocheilus is geographically, phenotypically, and genetically distinguishable from these two species. Cyprinella leptocheilus is confined to the Sand Hills and Coastal Plain regions of the Carolinas, whereas C. labrosa and C. zanema are more widely distributed in the Piedmont and Eastern Blue Ridge Foothills regions of the Santee River and Yadkin-Pee Dee River basins in the Carolinas and Virginia. Morphological differences detected were associated with the position of the dorsal-fin origin relative to the pelvic-fin origin; male tuberculation patterns and number of tubercles; upper lip thickness; mouth gape width; and the length of the maxillary barbel. Phylogenetic analyses of mitochondrial and mitochondrial-nuclear concatenated sequences consistently resolve each species as reciprocally monophyletic. Cyprinella leptocheilus is an evolutionary distinct sister to C. zanema; both are sister to C. labrosa. Within the C. leptocheilus clade, sequences from the Yadkin-Pee Dee River basin form a clade distinct from that of the Cape Fear River basin. These two clades are geographically isolated from one another. Given the divergence between the Cape Fear and Yadkin-Pee Dee River basins clades, it is recommended that these two C. leptocheilus clades receive protection as two evolutionarily significant units.
Keywords: Barbeled Cyprinella; Siouan Thinlip Chub; Leuciscidae